Verbal and Non-Verbal Communication: Insights from EFL Classroom Interactions - Muhamad, Holandyah; Erlina, Dian; Marzulina, Lenny; Herizal, Herizal; Putri, Hikmah Zalifah; Juniar, Farras (Indonesian Research Journal in Education |IRJE|, 2024)
This study aims to investigate the types and functions of verbal and non-verbal communication within an EFL classroom at SMA YPI Tunas Bangsa Palembang. A qualitative research methodology was employed for this study. The participants included a teacher and students from an English class, selected through purposive sampling. To collect data, the researchers utilized interviews and observations. Subsequently, the data gathered from the interviews and observations were transcribed and analyzed using thematic analysis. The results indicated that two types of verbal communication are employed by the teacher: oral and written. In addition to verbal communication, teachers typically utilize a variety of non-verbal communication methods, including facial expressions, body language and posture, gestures, eye contact, appearance, touch, and personal space. Furthermore, two primary functions of verbal communication can be identified, while several functions of non-verbal communication can be categorized. In verbal communication, these functions are defined to explain concepts clearly and to enhance students’ understanding. Conversely, the functions of non-verbal communication can be categorized as follows: conveying emotional signals, regulating the teaching mood, maintaining classroom control, expressing appreciation, capturing students’ attention, enhancing students’ focus, providing motivation, and emphasizing key points.